Cyclin-Dependent Kinase CRK9, Required for Spliced Leader trans Splicing of Pre-mRNA in Trypanosomes, Functions in a Complex with a New L-Type Cyclin and a Kinetoplastid-Specific Protein - Badjatia, Nitika; Park, Sung Hee; Ambrósio, Daniela L.; Kirkham, Justin K.; Günzl, Arthur (Public Library of Science (PLoS), 2016)
In eukaryotes, cyclin-dependent kinases (CDKs) control the cell cycle and critical steps in gene expression. The lethal parasite Trypanosoma brucei, member of the phylogenetic order Kinetoplastida, possesses eleven CDKs which, due to high sequence divergence, were generically termed CDC2-related kinases (CRKs). While several CRKs have been implied in the cell cycle, CRK9 was the first trypanosome CDK shown to control the unusual mode of gene expression found in kinetoplastids. In these organisms, protein-coding genes are arranged in tandem arrays which are transcribed polycistronically. Individual mRNAs are processed from precursor RNA by spliced leader (SL) trans splicing and polyadenylation. CRK9 ablation was lethal in cultured trypanosomes, causing a block of trans splicing before the first transesterification step. Additionally, CRK9 silencing led to dephosphorylation of RNA polymerase II and to hypomethylation of the SL cap structure. Here, we tandem affinity-purified CRK9 and, among potential CRK9 substrates and modifying enzymes, discovered an unusual tripartite complex comprising CRK9, a new L-type cyclin (CYC12) and a protein, termed CRK9-associated protein (CRK9AP), that is only conserved among kinetoplastids. Silencing of either CYC12 or CRK9AP reproduced the effects of depleting CRK9, identifying these proteins as functional partners of CRK9 in vivo. While mammalian cyclin L binds to CDK11, the CRK9 complex deviates substantially from that of CDK11, requiring CRK9AP for efficient CRK9 complex formation and autophosphorylation in vitro. Interference with this unusual CDK rescued mice from lethal trypanosome infections, validating CRK9 as a potential chemotherapeutic target.